KEMAMPUAN MENULIS TEKS BIOGRAFI PADA SISWA KELAS X MAN 1 PONTIANAK - Suryadi, Andi; Wartiningsih, Agus; Syahrani, Agus (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis study illustrates the ability to write biographical texts in class X MAN 1 Pontianak. The ability to write is to measure the ability of students to write biographical texts on aspects of content, structural aspects, and linguistic aspects. The subjects of this study were 112 students of class X MAN 1 Pontianak consisting of three classes namely X IPA 2, X IPS 3, and X IAI as samples. This data collection through the ability to write biographical text tests with the test questions in the form of essays as many as five questions in between the forms because the students determine the structure of biographical texts, determine aspects of content, and determine the aspects of language in written biographical texts. This type of research is quantitative descriptive Based on the data, the conclusion is the ability to write biographical texts in class X MAN 1 Pontianak. Being in the category is very high / satisfying because of 88 students consisting of three classes, X IPA 2, X IPS 3, and X IAI only 8 students who scored below the KKM (75.00) and there are about 80 students who get his grades for completeness KKM.Keywords: Ability to Write Biographical Texts